Knowledge Needs in Rehabilitation: Perspectives of Service Users and Professionals - Sipari, Salla; Tammelin, Mia; Helenius, Sari; Janhunen, Eija; Rantakokko, Merja; Vänskä, Nea; Harra, Toini (Frontiers in Rehabilitation Sciences, 2022)
Applying rehabilitation research knowledge in practice is challenging due to a gap between scientific knowledge produced by researchers and the needs of practical rehabilitation. This study describes the current and future knowledge needs of rehabilitation research from the perspectives of professionals and service users. We conducted a qualitative study with inductive content analysis from nine focus group interviews with rehabilitation stakeholders. The results show that current knowledge needs are strongly related to the meaningful and inclusive life of service users, the promotion of multi- and interprofessionalism in rehabilitation, and transdisciplinary applied research on rehabilitation. The future knowledge needs were related to the changing needs of rehabilitation and remote rehabilitation based on rapid change in society and digitalisation and on different rehabilitation practices and contexts. The results of the study can be used to enable favourable conditions for reciprocal research, development, and innovation (RDI) activities and research networks in transdisciplinary rehabilitation.